Valsalva ratio: a measure of stress in first year medical students - Loni, Shamshad Begum Abdul Razak (International Journal of Research in Medical Sciences, 2017)
Background: The Valsalva manoeuvre is commonly used as a method of assessing normal or disordered Autonomic control of Blood pressure and Heart Rate. Continuous changes in sympathetic and parasympathetic neural inputs exhibits alteration in Heart Rate and blood pressure which causes oscillation of R-R interval. Acute and short term stress leads to rapid changes throughout the body. Almost all body system gear up to meet the perceived dangers (stress).When healthy subjects are acutely stressed Heart rate increases and R-R interval on ECG decreases transiently. The purpose of the study is to see the changes in VMM in prestress and stress conditions. Methods: 56 non-smoking apparently healthy first year medical students (26 males and 26 females) were selected for the present study. Data collected two month prior to the examination as prestress values and during examination as during stress values. Data analyzed using Wilxcon Rank signed 2 tailed test and the sub groups data analyzed paired t test. Results: 11.54% males and 19.23% females had mild stress in prestress condition. During stress 46.15% males and 19.23% females had mild stress while 34.62% males and 57% of females had severe stress. The female had more stress as compared to males both in prestress and during stress conditions. Conclusion: We conclude that VR is affected by the academic stress in the first year medical students and that among them females are more affected which may be due to the new environment and new protocol of the education system.